District heating network maintenance planning optimization. (October 2021) - Pozzi, Matteo; Bettinelli, Andrea; Detassis, Fabrizio; Filippini, Ettore; Graziani, Simone; Morgione, Stefano; Vigo, Daniele
Abstract: To ensure the correct functioning of district heating networks and minimize critical failures, utilities allocate every year a significant part of their budget to maintenance operations. In the present work we describe a risk-based approach implemented to tackle the problem of designing optimal multi-year maintenance campaigns, applied to the Italian city of Brescia, showing how data-driven techniques can help decision makers assess the long terms impacts of budget allocations.